ANALISIS KINERJA AGEN ASURANSI SUN LIFE SYARIAH DI PT. SAHABAT SUKSES BERBISNIS SURABAYA - Selvia Maisyaro; Bowo Santoso (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of discipline, motivation and self-efficacy on the performance of Sun Life Syariah insurance agents at PT. Sahabat Sukses Berbisnis Surabaya. The population in this study uses all agents owned by the insurance company Sun Life Syariah at PT Sahabat Sukses Berbisinis Surabaya as many as 94 insurance agents. The sampling technique used was the saturated sampling technique so that all the population was sampled, obtained as many as 94 respondents. Data was collected through questionnaires, which were then processed using Partial Least Square (PLS) data analysis techniques by conducting validity tests, reliability tests, structural model tests and hypothesis testing. The results showed that discipline, motivation, and self-efficacy had a positive and significant influence on the performance of Sun Life Syariah insurance agents at PT. Sahabat Sukses Berbisnis Surabaya.